PEMEROLEHAN DAN PERKEMBANGAN BAHASA DALAM PENDIDIKAN SDIT MADANI AL-MUJAHIDIN - Nursalim; Susiandri; Jasril; M. Muda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the process of language acquisition and development of students at SDIT Madani Al-Mujahidin and the factors that influence it. The study used a qualitative approach with a descriptive approach. Data collection techniques included observation, interviews, and documentation. Observations were conducted during learning activities and student interactions within the school environment. Interviews were conducted with the principal, teachers, and several students to obtain more in-depth information regarding students' language abilities. Documentation was used to supplement the research data in the form of photos of activities, notes, and other supporting documents. The results showed that students' language acquisition and development were influenced by their family environment, school environment, peers, digital media, and reading habits. Students who received good language stimulation at home and at school tended to have better speaking, listening, reading, and writing skills. Teachers play a crucial role in supporting students' language development through the use of active and communicative learning methods, such as discussions, presentations, shared reading, role-playing, and question-and-answer sessions. Furthermore, the use of Indonesian, Arabic, and English within the school environment also provided students with experiences in acquiring more than one language. A supportive school environment and collaboration between teachers and parents are important factors in fostering optimal language development in students.